1998
DOI: 10.1001/jama.279.22.1789
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Supports and Education for the Prevention of Low Back Pain in Industry

Abstract: Context.-Low back pain is a frequent and costly health problem. Prevention of low back pain is important both for the individual patient and from an economic perspective. Objective.-To assess the efficacy of lumbar supports and education in the prevention of low back pain in industry. Design.-A randomized controlled trial with a factorial design. Setting.-The cargo department of an airline company in the Netherlands. Participants.-A total of 312 workers were randomized, of whom 282 were available for the 6-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
1
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 24 publications
1
83
1
5
Order By: Relevance
“…Of most potential concern to this review would be unreported (non-significant, small) behavioral outcomes, since we had concluded the body of behavioral evidence was strong. There were three studies (32,55,58) that measured health outcomes, indicating that they had an adequate timeline in which to measure behaviors yet did not report them. However, only one of the studies (55) made it to the final evidence synthesis stage (table 2), but its non-academic style of reporting and research setting (food retail) render it likely that behaviors were actually not measured.…”
Section: Examination Of Selective Reporting Of Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of most potential concern to this review would be unreported (non-significant, small) behavioral outcomes, since we had concluded the body of behavioral evidence was strong. There were three studies (32,55,58) that measured health outcomes, indicating that they had an adequate timeline in which to measure behaviors yet did not report them. However, only one of the studies (55) made it to the final evidence synthesis stage (table 2), but its non-academic style of reporting and research setting (food retail) render it likely that behaviors were actually not measured.…”
Section: Examination Of Selective Reporting Of Outcomesmentioning
confidence: 99%
“…A second issue is apparent in the lack of knowledge and attitudes outcome data available to this review, relative to behaviors and health outcomes data -a surprising finding, given the typically greater ease of collecting knowledge and attitudes data. There were seven studies (33,40,49,51,58,65,66) that collected behavioral or health information pre-and postintervention by questionnaire. Some of these questionnaires could presumably have measured knowledge and attitudes too.…”
Section: Future Researchmentioning
confidence: 99%
“…Working conditions are often presumed to play an important part in aetiology of back pain [4]. It is associated with working postures which included bending heavily with one's trunk, bending and twisting simultaneously with one's trunk, a bent and twisted posture for long periods, and making repetitive movements with the trunk [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A good example of external circumstances benefitting favourably is a study on the use of back support belts to prevent injuries among the baggage handlers who load aircraft at Amsterdam's Schiphol Airport (Van Poppel et al, 1998). This kind of work can cause back problems, but our study showed that back support belts were not effective in preventing these problems.…”
Section: Quality and Relevancementioning
confidence: 60%